Pharmacokinetics and Bioequivalence Study of a New Branded Generic Moxifloxacin Tablet Among Healthy Volunteers - Atiqah Amran; Ching Yee Tan; Ka-Liong Tan; Ranald Malcom Ho; Anil Kumar Anand; Chuei Wuei Leong (Wiley, 2024)
Indexed by WOS/SCOPUS